Use of the associative analysis for processing of scientific publications in the field of drugs delivery systems - О. А. Ugolnikova; Y. А. Demich; А. V. Lisitsa; V. Y. Kistanova; V. F. Kornyushko; А. I. Archakov; V. I. Shvets (Тонкие химические технологии)
In this paper the associative analysis of terms' co-occurrences in the abstracts of scientific articles (more than 600 thousands publications) in the field of drug delivery system was used. The associations between 2358 biologically active chemicals were depicted as a network diagram (semantic network). In the diagram clusters were found, which included compounds similar either in chemical structure or in biological properties. Most of the members of a certain cluster were investigated in relation to the problems of drug delivery.